Detection of Glycan Shedding in the Blood: New Class of Multiple Sclerosis Biomarkers? - DellaValle, Brian; Manresa-Arraut, Alba; Hasseldam, Henrik; Stensballe, Allan; Rungby, Jørgen; Larsen, Agnete; Hempel, Casper (Frontiers in Immunology, 2018)
Introduction: Multiple Sclerosis (MS) is a devastating autoimmune disease, afflicting people in the prime of their lives. Presently, after initial clinical presentation there are no reliable markers for whether a given patient will develop MS, or whether their prognosis will be aggressive or relapsing-remitting. Furthermore, many MS patients do not respond to treatment. Thus, markers for diagnosis, prognosis and treatment-responsiveness are lacking for a disease where a precision medicine approach would be valuable. The glycocalyx (GLX) is carbohydrate-rich outer surface of the blood vessel wall and is the first interaction between the blood and the vessel. We hypothesized that cleavage of the GLX may be an early stage predictor of immune attack, blood-brain barrier (BBB) breakdown, and disease severity in MS. Methods: Two experimental models of MS, experimental autoimmune encephalitis (EAE), were included in this study. EAE was induced in C57BL/6J mice and Lewis rats, which were monitored for weight loss and clinical presentation in comparison to healthy controls. Plasma samples were obtained longitudinally from mice until peak disease severity and at peak disease severity in rats. Soluble GLX-associated glycosaminoglycans (GAG) and proteoglycans (PG) were detected in plasma samples. Results: All animals receiving EAE emulsion developed fulminant EAE (100% penetrance). Increased plasma levels of chondroitin sulfate were detected before the onset of clinical symptoms and remained elevated. Hyaluronic acid was increased at the height of the disease, whereas heparan sulfate was transiently increased during early stages only. By contrast, syndecans 1, 3, and 4 were detected in EAE samples as well as healthy controls, with no significant differences between the two groups. Discussion: In this study, we present data supporting the shedding of the GLX as a new class of biomarker for MS. In particular, sugar-based GLX components are associated with disease severity in two models of MS; molecules that would not be detected in proteomics-based screens of MS patient samples. Patient studies are presently underway.